Water jet space charge spectroscopy: route to direct measurement of electron dynamics for organic systems in their natural environment. (1st July 2022) - Mittermair, Michael; Martin, Felix; Wörle, Martin; Bloß, Dana; Duensing, Andreas; Kienberger, Reinhard; Hans, Andreas; Iglev, Hristo; Knie, André; Helml, Wolfram
Abstract: The toolbox for time-resolved direct measurements of electron dynamics covers a variety of methods. Since the experimental effort is increasing rapidly with achievable time resolution, there is an urge for simple and robust measurement techniques. Within this paper prove-of-concept experiments and numerical simulations are utilized to investigate the applicability of a new setup for the generation of ultrashort electron pulses in the energy range of 300 eV up to 1.6 keV. The experimental approach combines an in-vacuum liquid microjet and a few-cycle femtosecond laser system, while the threshold for electron impact ionization serves as a gate for the effective electron pulse duration. The experiments prove that electrons in the keV regime are accessible and that the electron spectrum can be easily tuned by laser intensity and focal position alignment with respect to the water jet. Numerical simulations show that a sub-picosecond temporal resolution is achievable.